Cryptic enhancer elements in luciferase reporter vectors respond to the osteoblast-specific transcription factor Osf2/Cbfa1 - Thirunavukkarasu, K (BioTechniques, 2000)
Luciferase reporter vectors are commonly used for the functional analysis of basal promoter and enhancer elements of eukaryotic genes. Randomly occurring cisacting elements in the vector sequences that can spuriously respond to various transcription factors, combined with the high sensitivity of the luciferase assay system, could make these vectors unsuitable for functional studies with certain transcription factors. Here, we provide evidence that pGL2-Basic and pGL3-Basic are transactivated by the osteoblast-specific transcription factor Cbfa1 and estrogen receptor alpha probably through randomly occurring cisacting elements in the vector sequences. Our results highlight the limitations of pGL2-Basic and pGL3-Basic vectors in promoter transactivation/repression studies. The results also emphasize the need to perform appropriate controls and test the expression levels with a particular transcription factor and promoterless luciferase reporter vector combination